(3fXGe EdcJQhfi bGFe Ydi NQGFW GdJacjQ dJfejI HYV egGQGJ GdJacjQ GdHUQi h Gdage GdbQGFi dOi GdJdGejP GdeYGbjf SeYjG (B/ s - (3RjfH eMeO aJMi EHQGgje HfOGQis; (3MSjf HTjQ eMehO (B: s; (3SejQI CHhRjO fLOi (B: s; (3eMeO QaYJ MSf (B: s ((3GdbGgQI (B: s (3RjfH eMeO aJMi EHQGgje HfOGQi (B: s, 2018)
(3jgOa GdHMK GdMGdj Edi JUeje fXGe EdcJQhfi ebJQM bGFe Ydi NQGFW GdJacjQ h bjGS aYGdjJg Ydi JfejI HYV egGQGJ GdJacjQ GdHUQi h Gdage GdbQGFi dOi GdJdGejP GdeYGbjf SeYjG h jJchf GdfXGe GdEdcJQhfi GdebJQM GdbGFe Ydi NQGFW GdJacjQ ef efXheI EdcJQhfjI eJcGedI eJaGYdI; dEOGQI YedjJi GdJYdje h GdJYde Yf HYO(B: (3h jbhe GdHMK GdMGdi Ydi aQVjI aYGdjI fXGe GdEdcJQhfi GdebJQM GdbGFe Ydi NQGFW GdJacjQ dJfejI HYV egGQGJ GdJacjQ GdHUQi h Gdage GdbQGFj dOi JdGejP GdeYGbjf SeYjG(B: (3h dGNJHGQ gPg GdaQVjI Je GNJjGQ YjfI echfI ef (B(15) (3JdejP h JdejPg ehRYjf Ydi eOQSI GdCed ddUe h VYGa GdSeY HGdYHGSjI(B: (3h eOQSI GdCed ddUe h VYGa GdSeY HGdSjOI fajSI(B: (3ceG Je JWHjb GNJHGQJMUjdi(B: (3h HWGbI edGMXI dbjGS feh egGQGJ GdJacjQ GdHUQi(B: (3h GNJHGQ GdJMUjdi h HWGbI edGMXI dbjGS egGQGJ Gdage GdbQGFi(B. (3h dJWHjb gPg GdCOhGJ JhUdJ GdfJGFL Edi Jahb GdeLehYI GdChdi ai JfejI egGQGJ GdJacjQ GdHUQi h Gdage GdbQGFi(B: (3h CKHJJ aYGdjI GdfXGe GdEdcJQhfi GdebJQMs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe JcfhdhLjG GdJYdjes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJacjQ GdHUQis; (3NQGFW GdJacjQ GdEdcJQhfjIs; (3fXGe EdcJQhfis